Self-Supported Silicon Nanotube Arrays as an Anode Electrode for Li-Ion Batteries. (7th July 2017) - Tesfaye, Alexander T.; Gonzalez-Rodriguez, Roberto; Coffer, Jeffery L; Djenizian, Thierry
Abstract : We present the electrochemical performance of silicon nanotube vertical arrays possessing thin porous sidewalls as a negative electrode for Li-ion batteries. The Si nanotubes were fabricated by using sacrificial zinc oxide nanowire template on stainless steel substrate. Gravimetric capacity of 1670 mAh.g -1 was obtained after 30 cycles. The high capacity values are the result of the large active area offered by the porous Si nanotube array structures.